Water Clustering in Wheat Flour and Its Role in Water Diffusion: Observation Based on Sorption Isotherm - ZHAO Xuewei, WEI Xiaoxiao, GUO Yu, WANG Hongwei, ZHANG Hua, (Shipin Kexue)
This study was performed in order to investigate water clustering and its contribution to water diffusion in wheat flour. Based on the water adsorption and desorption isotherms of wheat flour at 20, 30 and 40 ℃, the water clustering properties were explored using the Park isotherm model, the Zimm-Lundberg method and the Brown method. Consistently, the results of the three methods suggested that water clustering occurred at high water activity (aw) levels, while the critical aw for clustering obtained from the three methods were only slightly different, ranging from 0.70 to 0.75, from 0.73 to 0.79 and from 0.56 to 0.68, respectively, which varied with temperature and the water sorption process. The predicted mean cluster size at aw of 0.95 was approximately 3.5, 4.5 and 6.5 from the three approaches, respectively. The number of water clusters kept almost unchanged at aw not lower than 0.90. Water diffusivity sharply decreased when aw was over 0.62–0.70. Furthermore, based on thermodynamic factor and self-diffusivity, it was found that water molecules were more likely to interact with themselves, leading to water clustering, which could be the major contributor to the sharp decrease of water diffusivity. When aw was equal to or more than 0.90, the strong self-diffusion capacity brought about by high water content could counteract the negative effect of water clustering, resulting in an almost constant water diffusivity.